Contributions of FDI, Import and Export in Economic Growth - Budha, Ramesh (NPRC Journal of Multidisciplinary Research, 2025)
Background: A nation’s economic output, measured by Gross Domestic Product (GDP), is influenced by a complex interplay of factors, including foreign direct investment (FDI), inflation, and international trade (imports and exports). For a developing, landlocked nation like Nepal, understanding the precise relationship between these variables is crucial for formulating effective economic policy and responding to external shocks. While FDI is often seen as a key driver of growth through capital infusion and technology transfer, its actual impact, alongside trade, requires empirical verification in the Nepalese context. Objective: This study aims to investigate the contributions of FDI, imports, and exports to Nepal’s economic growth. Its specific objectives are to examine the effect of foreign direct investment on economic growth and to analyze the interrelationships between inflation, exports, imports, and GDP. Methods: This research employs an analytical design using secondary annual time series data from 1970 to 2020, sourced from the Nepal Rastra Bank (NRB) and the World Bank. The relationship between the dependent variable (GDP growth rate) and independent variables (FDI, Inflation, Exports, Imports) was analyzed using Ordinary Least Squares (OLS) regression estimation via E-Views software. Findings: The regression results indicated a mixed relationship. A positive and statistically significant relationship was found between imports and GDP. Conversely, exports showed a significant but inverse relationship with GDP, with a 1% change in exports associated with a 6.36% reduction in GDP. The relationship between FDI and GDP was positive but not statistically significant. The model explained a high proportion of the variation in GDP (R-squared = 91%). However, the nonstationary nature of the variables and a low Durbin-Watson statistic (1.34) suggest potential bias in the regression, indicating possible spurious results. Conclusion: The study concludes that the relationships between key economic variables and growth in Nepal are complex and not always aligned with theoretical expectations. While imports appear to be positively associated with growth, the negative correlation with exports is counterintuitive and warrants further investigation. The findings suggest that a singular focus on attracting FDI or boosting exports may not be sufficient for ensuring economic growth. Implication: The results highlight the need for Nepalese policymakers to adopt a nuanced and multifaceted approach to economic management. Rather than relying on a single set of indicators, policies should be based on a comprehensive assessment of the interconnections between FDI, trade, and inflation. This research provides a basis for officials to better design targeted policies to enhance economic resilience and foster sustainable growth.